Development and validation of Islamic spirituality instrument / Abg Hamizam Abg Mohar, Ida Izumi Abdollah and Jasmine Vivienne Andrew - Abg Mohar, Abg Hamizam; Abdollah, Ida Izumi; Andrew, Jasmine Vivienne (Research Management Institute (RMI), 2013)
Spirituality has been predominantly studied in disciplines such as theology, psychology and sociology, and has developed relatively large numbers of spiritual instruments, these are however not suitable in the context of Islam. In Islam, spirituality is approached with a holistic concept, where the parameter of a Muslim's actions and behavior must be based on the Quran and Sunnah. A Muslim in performing all his daily activities thus must strive to harmonize and balance between the physical and spiritual demands of his existence that is seeking the pleasure of Allah, based on the Quran and Sunnah, - is a form Ibadah (worship). Thus this study has provided a new insight in the topic, which is based on the principles of Islam. This qualitative and quantitative study describes the methodological development of the instrument that captures the spiritual dimensions in Islam. The proposed 35 items instrument has been empirically tested for unidimensionality, reliability and validity using both exploratory and confirmatory factor analysis. Six factors were identified : namely deeds, relationships, harmony, self development, fairness and compliance were distinct and conceptually clear. Due to relatively lack of neither empirical data nor literatures on Islamic spirituality, the primary significance of this study serve as a valuable starting point for the development of Islamic spiritual instrument based on Islamic principles. On the micro aspect, the study contribute to the concept of spiritual in Islam where its parameter extends beyond the religion function, into their daily actions and behaviors. Its understanding will allow the Muslim to be on alert to behave in an acceptable manner. In addition, the instrument can act as a guidelines for institutions in development of activities that can enhances the spiritual element within the Islamic community.